Derajat Persaingan Industri Perbankan Indonesia: Setelah Krisis Ekonomi - Kusumastuti, Sri Yani (Journal of Indonesian Economy and Business, 2008)
This paper analyses the influence of economic crisis and the subsequent reforms on theÂ oligopolistic nature of the Indonesian banking industry. Since the crisis, there have beensubstantial changes in competitive environment. How did these changes affect a bankingÂ industry in which the three teen largest banks accounted for over 70 per cent of marketÂ share? To estimate the degree of competition, we apply Bresnahanâs (1989) conjecturalÂ variation model. Using estimation models based on microeconomic foundations, thisÂ method allows us to derive the index of the firmâs market power that is calculated as theÂ deviation of the market piece from the marginal coat as known as Lerner index. Theestimated indicates that the Lerner index showed a rising trend in the post-crisis period.Â This result indicates the possibility of a decline in the degree of competition.Keywords: Indonesian banking industry, degree of competition, BrenahanâsÂ conjectural variation, Lerner index.